2015
DOI: 10.1016/j.foodres.2014.10.032
|View full text |Cite
|
Sign up to set email alerts
|

Multispectral image analysis approach to detect adulteration of beef and pork in raw meats

Abstract: The aim of this study was to investigate the potential of multispectral imaging supported by multivariate data analysis for the detection of minced beef fraudulently substituted with pork and vice versa. Multispectral images in 18 different wavelengths of 220 meat samples in total from four independent experiments (55 samples per experiment) were acquired for this work. The appropriate amount of beef and pork-minced meat was mixed in order to achieve nine different proportions of adulteration and two categorie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
76
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(81 citation statements)
references
References 35 publications
1
76
0
2
Order By: Relevance
“…Compared with hyperspectral imaging, less processing time make MSI easer to meet the speed requirement of industrial production lines used for online high-throughput screening to assess meat quality, nutrition, safety, and authenticity. In recent years, MSI technology as a rapid and nondestructive analysis method has been wildly applied in fishes (Dissing, Nielsen, Ersbøll, & Frosch, 2011), meats (Ma et al, 2014a;Ropodi, Pavlidis, Mohareb, Panagou, & Nychas, 2015), fruits (Lunadei, Galleguillos, Diezma, Lleó, & Ruiz-Garcia, 2011), vegetables (Løkke, Seefeldt, Skov, & Edelenbos, 2013), etc. However, almost all of these studies only utilized spectral data without incorporating information on spatial data, which has been successfully used to improve the accuracy of model prediction in hyperspectral imaging studies (He, Wu, & Sun, 2014;Pu, Sun, Ma, & Cheng, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with hyperspectral imaging, less processing time make MSI easer to meet the speed requirement of industrial production lines used for online high-throughput screening to assess meat quality, nutrition, safety, and authenticity. In recent years, MSI technology as a rapid and nondestructive analysis method has been wildly applied in fishes (Dissing, Nielsen, Ersbøll, & Frosch, 2011), meats (Ma et al, 2014a;Ropodi, Pavlidis, Mohareb, Panagou, & Nychas, 2015), fruits (Lunadei, Galleguillos, Diezma, Lleó, & Ruiz-Garcia, 2011), vegetables (Løkke, Seefeldt, Skov, & Edelenbos, 2013), etc. However, almost all of these studies only utilized spectral data without incorporating information on spatial data, which has been successfully used to improve the accuracy of model prediction in hyperspectral imaging studies (He, Wu, & Sun, 2014;Pu, Sun, Ma, & Cheng, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Also, the results in [7][8][9] showed that an HSI system is able to provide significant information for performing classification in a plurality of applications for meat, such as detection of adulteration of minced meat [7], detection of chicken adulteration in minced beef [8], and lamb muscle discrimination [9]. In all of these studies, the models produced misclassification of pixels in pixel-based prediction, although they performed well in the case of sample-based prediction.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Thus, it provides a powerful model which takes the local variation in the image into account. In HSI for meat processing [4][5][6][7][8][9], the used strategy is averaging all pixels in the region of interest (ROI) as a spectral signature of the ROI. In this case, the resulting models consider only the spectral features to be used, while the spatial features were ignored.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Meat and meat products are important food commodities that have been targets for adulteration in the past and, whether deliberately or accidentally, undeclared admixtures and previously unknown and unpredictable adulterants have been observed. While some of these cases include substitution or partial substitution of high commercial value food commodities with cheaper ones, such as beef adulteration with pork or offal or by adding proteins from several origins (Kamruzzaman, Makino, & Oshita, 2015;Ropodi, Pavlidis, Mohareb, Panagou, & Nychas, 2015;Tian, Wang, & Cui, 2013;Zhao, Downey, & O'Donnell, 2014), non-compliance to label has not only economic, but also quality, safety and socio-religious consequences (Alamprese, Casale, Sinelli, Lanteri, & Casiraghi, 2013).…”
Section: Introductionmentioning
confidence: 99%